6th Annual Poly Royal Program (1938)
The official program for Poly Royal in 1938, created by students organizing Poly Royal. Includes a map of campus with activities, a schedule of Poly Royal, and other information about the school and the event. Includes signatures of students involved in Poly Royal. The theme for Poly Royal was 'Follow Poly's Progress.' See a full scan of the map (ua-sel_00000391) here: https://digital.lib.calpoly.edu/rekl-11949